219 The Effect of Introducing In-house Radiographers Out of Hours on Door to CT Times for FAST Positive Patients. (16th September 2019) - Hobson, Helen; Cogan, Nicola; Greene, Suzanne; Ryan, Dan
Abstract: Background: Stroke is a leading cause of death and disability in Ireland with up to 7, 000 people hospitalised following a stroke annually (IHF/HSE 2016). Every minute in which a large vessel ischaemic stroke is left untreated equates to the average patient losing 1.9 million neurons (Saver, 2006). With the introduction of out of hours in-house radiographers our aim was to look at how this impacted on the service of care to FAST positive patients who present to our Emergency Department. Stroke is a medical emergency where urgent assessment and treatment can lead to improved survival and reduced disability. Methods: To assess the impact of the introduction of in-house radiographers out of hours we compared door to CT times of FAST positive patients who presented to ED out of hours pre and post the introduction of in-house radiographers. We took the first 30 FAST calls following the introduction of the in-house radiographers and compared those times to the last 30 FAST calls prior to their introduction. Results: Preliminary results have shown that the introduction of in-house radiographers has reduced the median time spent in the Emergency Department times prior to CT imaging. Current median door to CT times prior to the introduction of in-house radiographers was 27 minutes, the median door to CT time post introduction of in-house radiographers is 21 minutes, however full results are still awaited. Conclusion: The introduction of in-house radiographers out of hours has led to a quicker transition of patients from the Emergency Department to the CT department thus reducing door to CT times.